Effect of Non-Edible Biodiesel Physical and Chemical Properties as Microturbine Fuel - Tan E.S.; Kumaran P.; Indra T.M.; Yoshikawa K. (Elsevier Ltd, 2023)
Alternative fuels; Fossil fuels; Fuel oils; Fuels; Oils and fats; Proven reserves; Turbines; Calophyllum Inophyllum; Environment pollution; International standards; Micro turbine; Physical and chemical properties; physicochemical; Second-generation biodiesels; Temperature profiles; Biodiesel